Marketing and finance perceptions of return on marketing investment in South Africa - Backhouse, Kevin Sean (My University, 2012)
This research report investigates the finance and marketing perceptions of return on marketing investment (ROMI) in South Africa. Traditionally, at many organisations, marketing budgets have been determined using arbitrary measures. In addition, the effectiveness of the marketing department is often gauged on ‘soft’ metrics such as customer loyalty and satisfaction without any financial evidence to prove its value to the business. Due to these reasons in the current economic turmoil many marketing budgets have been cut significantly by CEOs and CFOs of organisations. This has led to calls throughout the business environment for greater marketing accountability with ROMI being touted as one possibly method of increasing this accountability and measuring marketing’s contribution to shareholder value. This research report investigates the current practice of measuring the effectiveness of the marketing department; and identifying the challenges and potential benefits of using return on marketing investment (ROMI) as a metric to measure this effectiveness, based on the various different perceptions of marketing and finance executives. Interviews comprising open-ended questions of a structured and semi-structured format were used to obtain the insights and perceptions of marketing and finance executives. Ten respondents from each population were interviewed at length regarding their perceptions of this contentious topic. From the research conducted it became apparent that companies in South Africa do not measure ROMI as defined but use a mixture of short-term quantitative metrics and longer term qualitative metrics to measure the effectiveness of the marketing department. In addition most of the respondents did not use any one method consistently. There appears to be significant confusion regarding measuring marketing’s effectiveness in general and ROMI specifically. Whilst there are numerous benefits associated with measuring marketing via ROMI the obstacles surrounding its wide-spread adoption are significant. The results of the research discovered some interesting findings particularly regarding the differences and similarities in the perceptions of marketing and finance executives. In many instances both parties actually have similar views, however it is clear that better financial education of marketing executives and improved inter-department communication are key to successfully align these two (often warring) departments. It is clear that ROMI in South Africa is not the ‘silver metric’ some academics refer to it as, but something that can be rather used in combination with other metrics provided the process and method of calculation is simplified considerably.
MBA thesis - WBS
Keywords: Return on marketing investment; Marketing